2020
DOI: 10.1186/s13075-020-02175-2
|View full text |Cite
|
Sign up to set email alerts
|

Gout is associated with an increased risk for incident heart failure among older adults: the REasons for Geographic And Racial Differences in Stroke (REGARDS) cohort study

Abstract: Background: Gout has been associated with a higher risk for coronary heart disease (CHD) and stroke in some prior studies. Few studies have assessed the association of gout with incident heart failure (HF). Methods: We analyzed data from 5713 black and white men and women ≥ 65.5 years of age in the populationbased REasons for Geographic And Racial Differences in Stroke (REGARDS) cohort study who had Medicare coverage without a history of HF, CHD, or stroke at baseline between 2003 and 2007. Gout was defined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 52 publications
2
19
0
Order By: Relevance
“…Hyperuricaemia has been linked with an increased incidence of both coronary heart disease (CHD) and cerebrovascular accident (CVA) [6,7]. Several studies have found gout to be associated with an increased risk of cardiovascular diseases, such as CHD and CVA, but the evidence is conflicting [8][9][10][11]. Furthermore, there have been no previous reviews assessing the prevalence of venous thromboembolism (VTE) in patients with gout.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperuricaemia has been linked with an increased incidence of both coronary heart disease (CHD) and cerebrovascular accident (CVA) [6,7]. Several studies have found gout to be associated with an increased risk of cardiovascular diseases, such as CHD and CVA, but the evidence is conflicting [8][9][10][11]. Furthermore, there have been no previous reviews assessing the prevalence of venous thromboembolism (VTE) in patients with gout.…”
Section: Introductionmentioning
confidence: 99%
“…In the studies in younger populations with mean a age og <50 years old, urate-lowering therapy was associated with lowered coronary artery disease and stroke hospitalization, but not heart failure hospitalization, compared to non-urate lowering therapy in gout patients ( 16 , 17 ). In particular, gout was associated with an increased risk of HF, rather than an increased incidence of coronary heart disease, stroke, or all-cause mortality, in the REasons for Geographic And Racial Differences in Stroke (REGARDS) cohort study ( 18 ). Meanwhile, serum uric acid level was known to be associated with incident cardiovascular events and could be an important prognostic factor for patients with HF ( 19 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to current studies, hyperuricemia is associated with population mortality [27], affects the occurrence and progression of heart and kidney disease, and can be used as a predictor of obesity and metabolic syndrome [28][29][30]. A cohort study of people with heart failure found that hyperuricemia increases the risk of progression in patients with heart failure [31]. In our study, we found that the plasma levels of S-Klotho may have a protective effect against hyperuricemia in middle-aged and elderly people, so it is important to understand the effect of S-Klotho on hyperuricemia for middle-aged and elderly people, as well as clarify the potential bene ts and risks of S-Klotho in these population groups.…”
Section: Discussionmentioning
confidence: 99%